Association of preoperative systemic inflammation score with clinicopathological feature in the early stage of carcinoma cervix - Naher, Syfun; Begum, Shirin Akter; Akter, Naznine; Khatoon, Farhana; Nihar, Fatema; Meher, Subrina; Sultana, Fahmida; Hossen, Mofazzal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Cervical cancer is a significant global health concern, particularly in its early stages (stage IA-IIA). Systemic inflammation’s influence on cancer has been explored extensively in other tumor types, its association with clinicopathological features in early-stage carcinoma of the cervix remains a relatively underexplored area. This study aimed to evaluate the association of preoperative systemic inflammation score with clinicopathological features in the early stage of carcinoma cervix. Methods: This was a cross-sectional study that was carried out in the department of gynecological oncology at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh during the period from June 2022 and July 2023. In our study, we included 90 cervical cancer stage IA-IIA patients who underwent primary radical hysterectomy with bilateral pelvic lymphadenectomy. Results: Among all study participants, the mean age was 45.1±9.03 years. Majorities (65.6%) were found taking oral contraceptive pills. Higher SIS scores were strongly associated with larger tumor sizes, with mean tumor sizes of 1.45 cm (SIS 0), 1.99 cm (SIS 1), and 2.54 cm (SIS 2), respectively. Additionally, the incidence of lymphovascular space invasion (LVSI) demonstrated a pronounced increase with higher SIS scores, with 7.7% (SIS 0) and 92.3% (SIS 1-2) exhibiting LVSI. These associations were statistically significant (p<0.05). Conclusions: The study findings conclude that there is an association of pretreatment systemic inflammation score SIS with tumor size, lymphovascular space invasion, and increased depth of stromal invasion. SIS preoperatively can predict the clinicopathological risk factor of cancer cervix.